OP22 Factors independently associated with fatigue in IBD: Results from the baseline dataset of the PREdiCCt study. (27th May 2021) - Derikx, L; Siakavellas, S; Derr, L; Williams, L; Nikolas, P; Jenkinson, P; Lucaciu, L; Constantine-Cooke, N; Covil, K; Murdoch, L; Jones, G R; Lees, C
Abstract: Background: Fatigue is one of the most common symptoms in IBD resulting in decreased quality of life, impaired work productivity, and higher societal costs. However, little is known about its etiology and pathophysiology. We aimed to estimate the prevalence of fatigue and to identify predictive factors for fatigue. Methods: The PREdiCCt study (https://www.predicct.co.uk ) is the largest prospective study of the causes of IBD flare. 2629 patients in clinical remission were recruited from 48 UK sites. 1946 (74%) patients completed the baseline questionnaires. We assessed the prevalence of fatigue at baseline using a single item from the IBD Control questionnaire. To identify predictors for fatigue, we performed univariable and multivariable analyses including demographic, biochemical, environmental and psychosocial factors such as anxiety and depression [HADS], sleep quality [PSQI] and physical exercise [GPAQ]). Results: 759/1919 IBD patients in clinical remission (39.6%) reported fatigue in the past 2 weeks, while 1034 patients (53.9%) did not report fatigue. Patients who reported fatigue were more frequently female, had more frequently CD, and were more frequently smokers (Table 1). Univariable comparisons showed higher inflammatory markers in the fatigued group, with fewer patients in clinical remission. Multivariable analyses identified female sex (OR 2.4), CRP>5 (OR 2.1), bad sleep quality (OR 2.5), anxiety (OR 1.8) and depression (OR 6.2) as independent factors associated with fatigue (Table 2). Conclusion: We show the significant burden of fatigue in IBD patients and describe putative causes which demonstrate both the impact of residual gut inflammation and the relationship between fatigue and psychological well-being. The impact of environmental and dietary factors on fatigue is being further investigated with ongoing longitudinal data collection in the PREdiCCt study.